New red giants in NGC 6791 and NGC 6819 using Kepler superstamps - Covelo-Paz, Alba; Themeßl, N.; Espinoza-Rojas, Francisca; Hekker, Saskia (Astronomy and astrophysics, 2023)
Context: Stars that are members of stellar clusters are assumed to be formed at the same time and place from material with the same initial chemical composition. These additional constraints on the ensemble of cluster stars make these stars suitable as benchmarks. Aims: We aimed (1) to identify previously unknown red giants in the open clusters NGC 6791 and NGC 6819, (2) to extract their asteroseismic parameters, and (3) to determine their cluster membership. Methods: We followed a dedicated method based on difference imaging to extract the light curves of potential red giants in NGC 6791 and NGC 6819 from Kepler superstamp data. We extracted the asteroseismic parameters of the stars that showed solar-like oscillations. We performed an asteroseismic membership study to identify which of these stars are likely to be cluster members. Results: We found 149 red giant stars within the Kepler superstamps, 93 of which are likely cluster members. We were able to find 29 red giants that are not primary targets of Kepler, and therefore, their light curves had not been released previously. Five of these previously unknown red giants have a cluster membership probability greater than 95%.
Online veröffentlicht: 29. November 2023
Gesehen am 03.04.2024